Pendekatan Pengurus dalam Menggerakkan Kegiatan Majelis Taklim - Rahman, Budi Satria; Jamna, Jamaris (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the high activity of the Cleric of Nurul Ikhlas in Polonia, Air Tawar Timur Village, Padang Utara District, Padang City. The high level of activity of the Majelis Takhlim Nurul Ikhlas is alleged because the approach taken by the board was very good, the mobilization was very good, and the activities carried out went very well. The purpose of this research is to describe the approach used by the management in moving the activities of the Majelis Takhlim Nurul Ikhlas. This research is descriptive quantitative research. The population in this study were 105 members of Majelis Takhlim Nurul Ikhlas, as well as 40 samples. The sampling technique used was random sampling. The data collection tool used was a questionnaire, data analysis techniques using the percentage formula. The results showed that the management's approach to mobilizing the activities of the Majelis Takhlim was viewed in terms of (a) the approach taken by the management was very well done, (b) the mobilization carried out by the management could run very well, and (c) the activities of Majelis Takhlim went very well.